The correlation between vitamin D and inflammatory indicators in middle-aged and elderly patients with idiopathic membranous nephropathy: Vitamin D and inflammatory indicators - Lu, Zuojie; Dai, Shimin; Qin, Lingyan; Nong, Bo; Huang, Cuibo; Huang, Zhihu (Cellular and Molecular Biology, 2022)
This study investigates the relationship between vitamin D and inflammatory indicators in middle-aged and elderly patients with idiopathic membranous nephropathy (IMN). In this study, 100 middle-aged and elderly patients with IMN were enrolled in the nephropathy group and 100 healthy people were enrolled as a control group. The clinical data and test specimens were collected. The patients were categorized into deficiency group and lack group based on vitamin D level. The levels of serum vitamin 25 (OH) D, inflammatory indicators and clinical indicators were compared between the nephrotic group and the control group. The levels of inflammatory indicators and clinical indicators were compared. Pearson correlation analysis was applied to detect the correlation degree between serum vitamin 25 (OH) D, inflammatory indicators and clinical indicators in IMN patients. The outcomes compared with the control group, the levels of vitamin 25 (OH) D, IL-10, IFN-γ and ALB in the nephrotic group were significantly lower and CRP, IL-6, TNF-α, Cr, CysC, β2-MG were significantly higher (all p<0.05). Compared with the vitamin D deficiency group, the levels of IL-10, IFN-γ and ALB were significantly lower and NLR, CRP, IL-4, IL-6, TNF-α, 24 urinary protein, Cr, CysC, β2-MG were significantly higher in the vitamin D lack group (p<0.05). Vitamin 25 (OH) D level was negatively correlated with CysC, β2-MG, 24hUP, CR (r=-0.412, -0.387, -0.382, -0.429, all p<0.05) and was positively correlated with ALB (r=0.463, p<0.001). the conclusion Low vitamin D level in middle-aged and elderly patients with IMN is common and vitamin D supplementation can improve the clinical symptoms and delay the development of IMN.